A genome-wide transcriptional network controlled by the human SETMAR protein - Tellier, Michael (2015)
Transposable elements are discrete segments of DNA, which can be mobilized and amplified within a host genome. They are found in almost every living organism where their activities can contribute to gene expression and phenotypic variability. Hsmar1, a DNA transposon from the ITm superfamily, has entered the anthropoid primate lineage 55 to 65 Mya and remained active for ~ 15 My. The human genome contains 8,527 Hsmar1 remnants, which are essentially distributed between Made1 elements, an 80 bp deletion-derivative of the Hsmar1 transposon containing two transposon ends, and solo ITRs, which are deletion-derivative of Made1. Amidst these remnants, a fusion event between a pre-existing histone methyltransferase gene and one copy of the Hsmar1 transposase gave birth to the SETMAR gene. Except for a possible role in non-homologous end joining, the functions of SETMAR in human cells are still poorly understood. Since the DNA-binding domain of SETMAR is under purifying selection and several thousands transposon ends are located within genes, I investigated whether SETMAR binds to the genic transposon ends to regulate gene expression by dimethylating the K36 of histone H3. By using RNA-Seq, I established that a change in SETMAR expression modifies the expression of a third of the 1,523 protein-coding genes containing an ITR, with a bias towards up-regulation. I determined SETMAR binding sites with ChIP-Seq and found that SETMAR binds essentially to genic and intergenic Made1 elements and to a group of putative miRNAs derived from Made1. Even though only 2% of the differentially expressed genes with an ITR are found in the ChIP-Seq data, the genic ChIP peaks are enriched in the genes with an ITR. SETMAR may fine-tune by itself or by interacting with other proteins the expression of the subset of genes, which are differentially expressed and bound by SETMAR. Members of this group of genes encode proteins involved in signalling pathways such as FAM83B and ARSG, which could in turn modify gene expression. SETMAR could also potentially regulate the expression of the miRNAs-like derived from Made1.